Ответ:
a) (x-2)²-1
b) (x-1)(x-3)
Объяснение:
a) x²-4x+3=x²-4x+4+3-4=(x²-4x+4)+3-4=(x-2)²-1
b) вариант решения 1
x²-4x+3=0
D=4²-4*3=4
√D=2
x₁=(4-2)/2=1
x₂=(4+2)/2=3
x²-4x+3=(x-1)(x-3)
вариант решения 2
x²-4x+3 = x²-3x -x +3 = x(x-3) -(x-3)= (x-1)(x-3)
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Verified answer
Ответ:
a) (x-2)²-1
b) (x-1)(x-3)
Объяснение:
a) x²-4x+3=x²-4x+4+3-4=(x²-4x+4)+3-4=(x-2)²-1
b) вариант решения 1
x²-4x+3=0
D=4²-4*3=4
√D=2
x₁=(4-2)/2=1
x₂=(4+2)/2=3
x²-4x+3=(x-1)(x-3)
вариант решения 2
x²-4x+3 = x²-3x -x +3 = x(x-3) -(x-3)= (x-1)(x-3)